2012
DOI: 10.3168/jds.2012-5502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium salts of polyunsaturated fatty acids on productive and reproductive parameters of lactating Holstein cows

Abstract: Two experiments evaluated milk production, serum progesterone and insulin, and reproductive performance of lactating Holstein cows receiving or not receiving Ca salts of polyunsaturated fatty acids (PUFA), or receiving Ca salts of PUFA at different daily frequencies. In experiment 1, 1,125 cows randomly distributed in 10 freestall barns were enrolled. Barns were assigned randomly to receive a high-concentrate diet containing (PF) or not containing (control, CON) 1.1% (dry matter basis) Ca salts of PUFA. Diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
7
25
1
1
Order By: Relevance
“…Fouladi-Nashta et al (2007) only observed a tendency for greater P 4 concentrations when lactating dairy cows were fed 0.80 kg/d of calcium salts of FA compared with 0.20 kg/d. The results of the present study are in agreement with Lopes et al (2009) and Reis et al (2012), who did not observe increase in serum P 4 concentrations by adding calcium salts of PUFA at approximately 0.20 kg/cow daily. Taking these results together, it is possible that adding 0.22 kg of PF did not result in sufficient amounts of PUFA to decrease the hepatic clearance of P 4 .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Fouladi-Nashta et al (2007) only observed a tendency for greater P 4 concentrations when lactating dairy cows were fed 0.80 kg/d of calcium salts of FA compared with 0.20 kg/d. The results of the present study are in agreement with Lopes et al (2009) and Reis et al (2012), who did not observe increase in serum P 4 concentrations by adding calcium salts of PUFA at approximately 0.20 kg/cow daily. Taking these results together, it is possible that adding 0.22 kg of PF did not result in sufficient amounts of PUFA to decrease the hepatic clearance of P 4 .…”
Section: Discussionsupporting
confidence: 82%
“…Although there is evidence that feeding fatty acids improved the energy status of lactating dairy cows (Staples et al, 1998), an enhanced reproductive performance may occur apart from an improved energy status of the animals (Sklan et al, 1991). In agreement, Reis et al (2012) reported that feeding calcium salts of polyunsaturated fatty acids (PUFA) at 1.1% of diet DM to lactating dairy cows did not affect DM or energy intake, but decreased pregnancy losses compared with control cows that did not receive PUFA supplementation.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations